The Influence of Price Perception, Perceived Ease of Use, and Perceived Risk on Consumer Purchasing Decisions on TikTok Shop in Surakarta - Adhiyani, Oryza Rully; Winarni, Selo (Pascasarjana STIE Amkop Makassar, 2025)
This study examines the factors influencing consumer purchasing decisions on TikTok Shop in Surakarta, focusing on price perception, perceived ease of use, and perceived risk. Using a quantitative approach, data were collected from 100 respondents and analyzed through multiple regression analysis, t-tests, and F-tests. The results indicate that price perception (p = 0.004) and perceived ease of use (p = 0.030) significantly influence purchasing decisions, while perceived risk (p = 0.000) has the strongest impact, reflecting consumer concerns about security and product authenticity. The F-test (p = 0.000) confirms that all three factors simultaneously affect consumer purchasing behavior. Additionally, the correlation coefficient (R = 0.729) indicates a strong relationship between the independent variables and purchasing decisions, while the coefficient of determination (R² = 0.531) suggests that 53.1% of purchasing decisions are influenced by these variables, with the remaining 46.9% explained by other factors. These findings highlight the necessity for competitive pricing, user-friendly interfaces, and trust-enhancing measures to optimize consumer engagement in social commerce. Future research should explore additional variables such as brand trust, social influence, and digital marketing strategies to provide a more comprehensive understanding of consumer behavior in online marketplaces. Keywords: Price Perception, Perceived Ease of Use, Perceived Risk, Consumer Purchasing Decisions, Social Commerce, TikTok Shop